2020
DOI: 10.3390/su12166379
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Olive Oil Consumers Based on Consumption and Preferences toward Extrinsic, Intrinsic and Sensorial Attributes of Olive Oil

Abstract: The aim of this paper was to identify and describe segments of a study population that consumes olive oil. Therefore, a survey was conducted in 2019 on a sample of 705 German and 175 UK consumers. In both samples, three consumer segments were identified. These three segments differed significantly with regard to purchase and consumption patterns, as well as attitudes toward the extrinsic, intrinsic, sensorial, and health attributes of olive oil. Their main preferences related to health properties of olive oil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Nevertheless, consumers’ preferences concern not only the agricultural and production processes, but a complex set of product attributes [ 2 ]. Among these are the perceived sensorial quality of olive oil, such as taste, acidity, and fragrance, but also color, country of origin, geographical indication (GI), and the use of olives from organic farming [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, consumers’ preferences concern not only the agricultural and production processes, but a complex set of product attributes [ 2 ]. Among these are the perceived sensorial quality of olive oil, such as taste, acidity, and fragrance, but also color, country of origin, geographical indication (GI), and the use of olives from organic farming [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the literature findings highlights heterogeneity in olive oil consumption habits not only between traditional new consumer countries, but also across Mediterranean countries (see in particular [ 3 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]). For instance, Dekhili et al [ 40 ] point out the relevance of oil color in Tunisia and France, while Ribeiro and Santos [ 41 ] focus on Portuguese consumers’ preference for low-acidity oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike RO and SO, olive trees only grow in a Mediterranean like climate and therefore must be imported to countries out with that area [ 16 ]. Both age and income level are key factors that influence the frequency and amount of olive oil consumed in the UK, with higher income brackets and lower age groups (below 50 years old) contributing most to frequent and occasional olive oil consumption in the UK [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in numerous studies about olive oil attributes, the concept of country of origin was highlighted as a significant feature for olive oil and other products, such as French wines and cheeses; German beer; Swiss and Belgian chocolate; and Italian wine, cheese, and pasta. Moreover, recent studies on food products have also shown the importance of the country of origin and suggested that a certain product image reflects the image of the region or country of production [8]. Therefore, each olive oil producing country should study their SD as a specific case study.…”
Section: Introduction 1background and Research Motivationmentioning
confidence: 99%